Computer Vision for Real-Time Control in Drying - Martynenko, Alex (Food engineering reviews, 2017)
The range of applications of computer vision for product inspection, monitoring, and control in drying in both offline and online modes are reviewed. The basics of computer vision, image acquisition, processing, pattern recognition, and learning are discussed. General approach to interpretation of computer vision data, relevant to drying process, is proposed. Examples of process control, based on computer vision as “intelligent” observer, are provided. Real-time imaging, data processing, and analysis make computer vision an excellent tool for feedback control of drying.